2020
DOI: 10.3390/membranes10110351
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Water-Permeable Chitosan Membranes on Chitosan Molecular Weight and Alkali Treatment

Abstract: Chitosan membranes were prepared by the casting method combined with alkali treatment. The molecular weight of chitosan and the alkali treatment influenced the water content and water permeability of the chitosan membranes. The water content increased as the NaOH concentration was increased from 1 to 5 mol/L. The water permeation flux of chitosan membranes with three different molecular weights increased linearly with the operating pressure and was highest for the membrane formed from chitosan with the lowest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
(23 reference statements)
1
7
0
1
Order By: Relevance
“…However, the chitosan-soluble complex showed changes in the surface. This is consistent with previous reports that demonstrate that alkali treatment changes the polymer network producing a rough porous surface (Nakayama et al, 2020;Gültan et al, 2021). The crosslinking of chitosan with SDS generated strong intermolecular interactions shown by spherical and slightly porous structures; this result is similar to those reported in other studies (Milinković Budinčić et al, 2021;Jiang et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
“…However, the chitosan-soluble complex showed changes in the surface. This is consistent with previous reports that demonstrate that alkali treatment changes the polymer network producing a rough porous surface (Nakayama et al, 2020;Gültan et al, 2021). The crosslinking of chitosan with SDS generated strong intermolecular interactions shown by spherical and slightly porous structures; this result is similar to those reported in other studies (Milinković Budinčić et al, 2021;Jiang et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
“…It appears that the lower WVTR may be due to the high molecular weight chitosan used for the lm preparation. Nakayama et al (2020) reported that the lm made of CS with a high molecular weight has the lowest water vapor permeability and therefore the decreased WVTR. 40 The GA functionalized CPG bio-lms exhibited a WVTR of 21.75, 19.02 and 19.04 g m −2 h −1 for CPG5%, CPG10% and CPG15%, respectively.…”
Section: Water Vapor Transmission Rate and Oxygen Permeabilitymentioning
confidence: 99%
“…Nakayama et al (2020) reported that the lm made of CS with a high molecular weight has the lowest water vapor permeability and therefore the decreased WVTR. 40 The GA functionalized CPG bio-lms exhibited a WVTR of 21.75, 19.02 and 19.04 g m −2 h −1 for CPG5%, CPG10% and CPG15%, respectively. The decreased WVTR trend was observed with the increase in GA content within the CS/PL matrices.…”
Section: Water Vapor Transmission Rate and Oxygen Permeabilitymentioning
confidence: 99%
“…Otros estudios muestran comportamientos similares con la incorporación de Cu(II) y otros cationes de diferente número de valencia y radio atómico (Avilés-Barreto & Suleiman, 2013;Guerrero-Gutiérrez & Suleiman, 2013;. Además, el entrecruzamiento del catión con los grupos iónicos induce una reducción en la cantidad de agua absorbida (Nakayama et al, 2020). Estos resultados se relacionan con la interacción del catión con los grupos funcionales mostrados con el ATR-FTIR que inducen cambios en el patrón de degradación en las membranas.…”
Section: Propiedades Químicas Térmicas Mecánicas Y óPticasunclassified